Peptoid‐Based Rare‐Earth (Group 3 and Lanthanide) Transporters. Issue 14 (15th April 2013) - Kölmel, Dominik K.; Rudat, Birgit; Schepers, Ute; Bräse, Stefan
Abstract: Group 3 and lanthanide metals have been complexed by peptoid transporters [polycationic oligo( N ‐substituted glycines)]. To achieve this, the rare‐earth‐complexing DTPA ligand was coupled with the peptoids, and afterwards lanthanide salts were added. The photopysical and biological properties of these complexes were investigated. Abstract : Oligo( N ‐substituted glycine) peptoids have been combined with various rare‐earth metals by means of the complexing DTPA ligand. The photophysical and biological properties of the resulting complexes have been investigated.